Pengaruh Penggunaan Chat GPT (Generative Pre-Trained Transformer) terhadap Rata-Rata Nilai IPK Mahasiswa Sekolah Tinggi Agama Buddha (STAB) Kertarajasa - Sujatmiko, Dian; Dhamayanti, Wina; Sastrosupadi, Adji (Jounal Nyanadassana, 2024)
The purpose of this study is to compare the effects on students at Kertarajasa College of Buddhism (STAB) before and after they used Chat GPT. The research design employed in this study is an experiment using a quantitative methodology. A questionnaire given to every student and the average GPA from batch 21's first and seventh semesters served as the research instrument. A Likert scale and a t-test will be used to assess the data gathered from the distribution of questionnaires in order to determine the average GPA score. The study's findings clarify why Chat GPT's degree of use has a positive impact. The evaluation, comprising 30 questions, yielded a total score of 5710 with a percentage achievement of 73.21%. In the partial assessment, the motivation aspect had a value of 1909 with a percentage achievement of 73.35%, the effectiveness aspect had a value of 1889 with a percentage achievement of 72.65%, and the technology aspect had a value of 1912 with a percentage achievement of 73.54%. Additionally, the average GPA value in the t-test showed a significance value of 2.61> t_0.05, indicating a very real effect of Chat GPT use on raising the average GPA value. As a result, measures must be taken to guarantee that this technology is exclusively utilized as a tool to help educators deliver better instruction.